Una Soluzione OS per la creazione di gestionali cartografici web basati su progetti QGIS - Cristiano Fattori (mediaGEO soc. coop., 2020)
As part of the management of reimbursement of damages from wildlife, the Direzione Capitale Naturale, Parchi ed Aree Protette of Regione Lazio made use of the OS G3WSUITE framework (based on QGIS-Server) for the creation of a web cartographic management system.